Film: Da'wah Method Opportunities - Owie, Anggra Agastyassa (UIN Fatmawati Sukarno Bengkulu, 2023)
Film is an audio-visual presentation that is used in various purposes. Film is not only used as a medium for entertainment, but can be used as a medium for preaching. Film in society is a unifier in life, a medium for communicating in society. In this study, the researcher hopes to be able to give birth to an analysis of films that can become opportunities as a method of da'wah. In this study, researchers used descriptive qualitative research, emphasizing data search using the library research method and using content analysis in carrying out data analysis techniques. The results in this study indicate that films are presented to the audience by means of collaboration between drama and music, by providing entertainment and information from existing behavioral and emotional guidelines. As a da'wah media, a film must contain three elements that must be present in the da'wah message/material, namely faith, morality and sharia. The requirements for a film to be submitted as a da'wah film are, that is, in accordance with sharia and must be logical. Film as a medium of da'wah has the advantage that through showing films it makes the audience pay close attention, making the audience discuss with each other after the screening is over to find the meaning of the message expressed. Through films, the message delivery will be more communicative. The message presented will make people remember what was conveyed more. As a propaganda medium, film is used to proclaim truth.